If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + 6(y + -9) = 0 Reorder the terms: y + 6(-9 + y) = 0 y + (-9 * 6 + y * 6) = 0 y + (-54 + 6y) = 0 Reorder the terms: -54 + y + 6y = 0 Combine like terms: y + 6y = 7y -54 + 7y = 0 Solving -54 + 7y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '54' to each side of the equation. -54 + 54 + 7y = 0 + 54 Combine like terms: -54 + 54 = 0 0 + 7y = 0 + 54 7y = 0 + 54 Combine like terms: 0 + 54 = 54 7y = 54 Divide each side by '7'. y = 7.714285714 Simplifying y = 7.714285714
| y=41x-(88000+33x) | | 7x+6x+3+8=10x+5+2x | | 13x+.64x=100 | | 6x-14-4x=6x-9 | | (4X+7)+(2X-16)= | | 7(4y-9)-(2y+6)= | | 3y-10=x | | u=5(8n+35)+6(n+1) | | 5n+9=3n-1 | | (4c^8d^-6)/8d^3)^-1 | | (4X+7)+(2-16)= | | 5m=18+2m | | log(9x)=1 | | (2+y)(2y+3)=0 | | x=-14+3(4) | | (-4.5)+4.9+3.4= | | 18+10=m | | 2.5x-3(x+1)=12 | | 4x^9n+4=256 | | -70+15y+2y=-2 | | 3/9y-5=-2 | | h=15-8 | | (-5)+(-7.1)= | | 8=-9x+3 | | 4x(5x+3)=2x(7x+6) | | ((60-61)/n)x100=60 | | [-14]= | | a+3b=30 | | 6x+2=8x-12 | | (4n-3)(2n+1)=7 | | 2a+7=23 | | -1/2=2/3v-2/7 |